Greek literacy in sixteenth‐century England. Issue 3 (20th October 2014) - Lazarus, Micha
Abstract : Recent scholarship has focused on close engagements with Greek literature in sixteenth‐century England, but must still contend with the conventional belief that Elizabethans had negligible Greek. The standard accounts on which this belief is based, however, have not kept pace with the last thirty years of developments in the history of Renaissance education; moreover, they have consistently evaluated Greek literacy by the incommensurate standards of Greek philological scholarship. This review of the multiform evidence of Greek language training in the sixteenth century suggests that Greek literacy was in fact more widespread and advanced in England than has been allowed, and establishes a new baseline and chronology of linguistic access for English readers in the period.